Creativity vs. Performativity for Inclusion: Teachers’ Attitudes in Greece - Tataraki, Despoina (2013)
In the rapidly changing world that we live in, where we cannot anticipate the social, political and financial developments even of the near future, education, one of the major signifiers of human development, cannot remain static. The aim of this research study is to accentuate the debate which has been ignited between traditional performative educational pedagogies and creative educational methods which have started gaining ground during the last years. Furthermore, it aims to explore the attitudes and views of Primary Education teachers (n=4) in Greece on several issues that arise from this debate through semi-structured interviews. Analysis showed that although teachers are eager to adopt and promote new creative teaching and learning methods, there are several constraints and dilemmas that should be overcome in practice. Moreover, it has been reported that creative approaches to teaching and learning have a very positive impact both on academic and socio-emotional development of students with or without special educational needs (SEN) and they are great contributors towards the inclusion of the former in the educational procedure.